Structural and Functional Analysis of Excised Skins and Human Reconstructed Epidermis with Confocal Raman Spectroscopy and in Microfluidic Diffusion Chambers - Dorottya Kocsis; Hichem Kichou; Katalin Döme; Zsófia Varga-Medveczky; Zsolt Révész; Istvan Antal; Franciska Erdő (Pharmaceutics, 2022)
Several ex vivo and in vitro skin models are available in the toolbox of dermatological and cosmetic research. Some of them are widely used in drug penetration testing. The excised skins show higher variability, while the in vitro skins provide more reproducible data. The aim of the current study was to compare the chemical composition of different skin models (excised rat skin, excised human skin and human-reconstructed epidermis) by measurement of ceramides, cholesterol, lactate, urea, protein and water at different depths of the tissues. The second goal was to compile a testing system, which includes a skin-on-a-chip diffusion setup and a confocal Raman spectroscopy for testing drug diffusion across the skin barrier and accumulation in the tissue models. A hydrophilic drug caffeine and the P-glycoprotein substrate quinidine were used in the study as topical cream formulations. The results indicate that although the transdermal diffusion of quinidine is lower, the skin accumulation was comparable for the two drugs. The various skin models showed different chemical compositions. The human skin was abundant in ceramides and cholesterol, while the reconstructed skin contained less water and more urea and protein. Based on these results, it can be concluded that skin-on-a-chip and confocal Raman microspectroscopy are suitable for testing drug penetration and distribution at different skin layers within an exposition window. Furthermore, obese human skin should be treated with caution for skin absorption testing due to its unbalanced composition.